Conceptual teaching of physics in secondary schools - Ülen, Simon; Mitja Slavinec, Mitja Slavinec; Gerlič, Ivan (Anali PAZU, 2022)
In last two decades many educational researchers have been searching for new appropriate methods of improving the educational process. Project COLOS (Conceptual Learning of Science) stimulates the exploitation of the didactical potential of modern technology for learning and teaching of science and physics in particular. Experimental investigation presented in this article tries to determine whether the conceptual learning and teaching of physics is more effective in comparison with traditional frontal teaching of physics. The main goal of our study was to examine the effects of conceptual learning and teaching of physics in the field of Electricity and Magnetism in the secondary school. The key finding of research was that the students, who were taught through the conceptual way, achieved better results than those who were taught traditionally.